Pseudo Almost Periodic Sequence Solutions of Discrete Time Cellular Neural Networks - Abbas, S. (Nonlinear Analysis: Modelling and Control, 2009)
In this paper we discuss the existence and uniqueness of a k-pseudo almost periodic sequence solutions of a discrete time neural network. We give several sufficient conditions for the exponential and global attractivity of the solution.
Keywords: pseudo almost periodic function; almost periodic sequence; cellular neural network; discrete time model